Pelatihan Digital Marketing E-Katalog LPSE di PT. Abisakti Surya Megakon [Digital Marketing Training on LPSE E-Catalog at PT. Abisakti Surya Megakon] - Firman Yudianto; Mukhtar Adinugroho; Nur Shabrina Meutia (UKInstitute, 2026)
The rapid development of information technology has encouraged companies to adopt digital transformation in marketing and procurement processes. One of the platforms used in government procurement is the LPSE E-Catalog, which enables transparent and efficient electronic transactions. PT. Abisakti Surya Megakon, as a provider of goods and services, faces challenges in optimizing the use of digital marketing through the LPSE E-Catalog, particularly in product management, digital promotion, and online marketing strategies. This community service activity aimed to improve the competencies of the company’s human resources in utilizing the LPSE E-Catalog as a digital marketing platform. The implementation methods included observation, training, mentoring, and evaluation. The results showed an increase in participants’ understanding of the LPSE E-Catalog, digital marketing strategies, product display optimization, and electronic transaction management. Furthermore, participants were able to independently implement digital marketing strategies to enhance the company’s opportunities in government procurement markets. This activity positively contributed to improving digital literacy and enhancing the company’s competitiveness in the era of digital transformation. Abstrak. Perkembangan teknologi informasi mendorong perusahaan untuk melakukan transformasi digital dalam proses pemasaran dan pengadaan barang/jasa. Salah satu platform yang digunakan dalam pengadaan pemerintah adalah E-Katalog LPSE yang memungkinkan proses transaksi dilakukan secara transparan dan efisien. PT. Abisakti Surya Megakon sebagai perusahaan penyedia barang dan jasa menghadapi kendala dalam optimalisasi pemanfaatan digital marketing berbasis E-Katalog LPSE, terutama pada aspek pengelolaan produk, promosi digital, dan strategi pemasaran daring. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi sumber daya manusia perusahaan dalam memanfaatkan E-Katalog LPSE sebagai media digital marketing. Metode pelaksanaan meliputi observasi, pelatihan, pendampingan, dan evaluasi. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai penggunaan E-Katalog LPSE, strategi pemasaran digital, optimasi tampilan produk, dan pengelolaan transaksi elektronik. Selain itu, peserta mampu mengimplementasikan strategi digital marketing secara mandiri untuk meningkatkan peluang pemasaran produk perusahaan pada sektor pengadaan pemerintah. Kegiatan ini memberikan dampak positif terhadap peningkatan literasi digital dan daya saing perusahaan dalam era transformasi digital.